ChatGPT in higher education: factors influencing ChatGPT user satisfaction and continued use intention - Yu, Chengcheng; Yan, Jinzhe; Cai, Na (Frontiers in Education, 2024)
Artificial intelligence (AI) chatbots, represented by ChatGPT, have shown significant improvement in natural learning and problem analysis and solving, which could trigger a profound change in the education sector and have a far-reaching impact on educational practices. This study aimed to gain insights into the various impacts on users' experience when using the AI tool ChatGPT in higher education. The study analyzed questionnaire data from 328 college students who used ChatGPT. Employing structural equation modeling, this study examined the technology acceptance model in the higher educational setting to identify factors influencing continued use of ChatGPT. The results show that ChatGPT's compatibility positively affected users' perceived ease of use and that efficiency positively affected perceived usefulness. Furthermore, perceived ease of use and perceived usefulness were identified as core factors affecting users' satisfaction and continued use intentions, with user satisfaction showing a significant positive effect on continued use intention. The findings not only provide new perspectives on human-computer interaction theory in higher education but also further refine the functions of current smart devices. This study will help to promote the continued progress and improvement of educational technology, while also deepening understanding of the relationship between attitude and behavior.